An analysis of total lightning characteristics in tornadic storms: preparing for the capabilities of the GLM - Reimel, Karly Jackson, author; Rutledge, Steven, advisor; Miller, Steven, advisor; Rasmussen, Kristen, committee member; Eykholt, Richard, committee member (Colorado State University. Libraries, 2017)
Numerous studies have found that severe weather is often preceded by a rapid increase in the total lightning flash rate. This rapid increase results from numerous intra-cloud flashes forming around the periphery of an intensifying updraft. The relationship between flash rates and updraft intensity is extremely useful to forecasters in severe weather warning decision making processes, but total lightning data has not always been widely available. The Geostationary Lightning Mapper (GLM) will be the first instrument to detect lightning from geostationary orbit, where it will provide a continuous view of lightning over the entire western hemisphere. To prepare for the capabilities of this new instrument, this thesis analyzes the relationship between total lightning trends and tornadogenesis. Four supercellular and two non-supercellular tornadic storms are analyzed and compared to determine how total lightning characteristics differ between dynamically different tornadic storms. Supercellular tornadoes require a downdraft to form while landspout tornadoes form within an intensifying updraft acting on pre-existing vertical vorticity. Results of this analysis suggest that the supercellular tornadoes we studied show a decrease in flash rate and a decrease in lightning mapping array (LMA) source density heights prior to the tornado. This decrease may indicate the formation of a downdraft. In contrast, lightning flash rates increase during landspout formation in conjunction with an intensifying updraft. The total lightning trends appear to follow the evolution of an updraft rather than directly responding to tornadogenesis. To further understand how storm microphysics and dynamics impact the relationship between lightning behavior and tornadogenesis, two of the tornadic supercells were analyzed over Colorado and two were analyzed over Alabama. Colorado storms typically exhibit higher flash rates and anomalous charge structures in comparison to the environmentally different Alabama storms that are typically normal polarity and produce fewer flashes. The difference in microphysical characteristics does not appear to affect the relationship between total lightning trends and tornadogenesis. The capabilities of GLM are yet to be determined because the instrument is still in its calibration/validation stages. However, as part of the GLM cal/val team, we were in a unique position to examine the first-light GLM data and contribute to the assessment of its performance for noteworthy thunderstorm events during the Spring/Summer seasons of 2017. The final chapter of this thesis displays a preliminary analysis of GLM data. A first look into GLM performance is established by comparing GLM data with data from other lightning detecting instruments. Overall, GLM appears to detect fewer flashes than other lightning detecting networks and instruments in Colorado storms, more so for intense storms compared to weaker storms.
Keywords: lightning; severe; GLM; tornado; meteorology